The UbiB family member Cqd1 forms a novel membrane contact site in mitochondria - Khosravi, Siavash; Chelius, Xenia; Unger, Ann-Katrin; Rieger, Daniela; Frickel, Johanna; Sachsenheimer, Timo; Lüchtenborg, Christian; Schieweck, Rico; Brügger, Britta; Westermann, Benedikt; Klecker, Till; Neupert, Walter; et al. (Journal of cell science, 2023)
Mitochondria are essential organelles of eukaryotic cells and are characterized by their unique and complex membrane system. They are confined from the cytosol by an envelope consisting of two membranes. Signals, metabolites, proteins and lipids have to be transferred across these membranes via proteinaceous contact sites to keep mitochondria functional. In the present study, we identified a novel mitochondrial contact site in Saccharomyces cerevisiae that is formed by the inner membrane protein Cqd1 and the outer membrane proteins Por1 and Om14. Similar to what is found for the mitochondrial porin Por1, Cqd1 is highly conserved, suggesting that this complex is conserved in form and function from yeast to human. Cqd1 is a member of the UbiB protein kinase-like family (also called aarF domain-containing kinases). It was recently shown that Cqd1, in cooperation with Cqd2, controls the cellular distribution of coenzyme Q by a yet unknown mechanism. Our data suggest that Cqd1 is additionally involved in phospholipid homeostasis. Moreover, overexpression of CQD1 and CQD2 causes tethering of mitochondria to the endoplasmic reticulum, which might explain the ability of Cqd2 to rescue ERMES deletion phenotypes.
Gesehen am 20.09.2023